Mineralized Osteochondritis Dissecans Cartilage Flap Mimicking Supraspinatus Tendon Mineralization - Beaver, D. P.; Hooper, C.; Nicoll, R. G.; Johnson, K. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
A four-year-old Labrador-mix dog had chronic forelimb lameness due to a mineralized osteochondritis dissecans cartilage flap that was adherent to the synovial membrane, deep to the supraspinatus tendon. This seems to be an unusual site for the lodgment of migrating flaps; most have been found in the caudal compartment of the shoulder joint or in the bicipital tendon sheath. Radiographically, the mineralized flap was indistinguishable from supraspinatus tendon mineralization, which is another cause of chronic lameness in adult large breed dogs.Mineralized cartilage within the shoulder was radiographi-cally indistinguishable from supraspinatus mineralization and caused chronic lameness.
Keywords: Osteochondritis dissecans; mineralized cartilage; tendon mineralization